4(-7-v)+6=-10-7v

Simple and best practice solution for 4(-7-v)+6=-10-7v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-7-v)+6=-10-7v equation:


Simplifying
4(-7 + -1v) + 6 = -10 + -7v
(-7 * 4 + -1v * 4) + 6 = -10 + -7v
(-28 + -4v) + 6 = -10 + -7v

Reorder the terms:
-28 + 6 + -4v = -10 + -7v

Combine like terms: -28 + 6 = -22
-22 + -4v = -10 + -7v

Solving
-22 + -4v = -10 + -7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '7v' to each side of the equation.
-22 + -4v + 7v = -10 + -7v + 7v

Combine like terms: -4v + 7v = 3v
-22 + 3v = -10 + -7v + 7v

Combine like terms: -7v + 7v = 0
-22 + 3v = -10 + 0
-22 + 3v = -10

Add '22' to each side of the equation.
-22 + 22 + 3v = -10 + 22

Combine like terms: -22 + 22 = 0
0 + 3v = -10 + 22
3v = -10 + 22

Combine like terms: -10 + 22 = 12
3v = 12

Divide each side by '3'.
v = 4

Simplifying
v = 4

See similar equations:

| a(9)=a^2 | | Y=-13x+12 | | y=(x+3)+1 | | 3x+41=x+75 | | 2-2x=5x-61 | | 3p^2-14=80 | | 2.4(8x-4)+1.8(-6x-18)+9.6=-0.6(-16x+64) | | 3x/5=7/11 | | {1/2} | | -x^4+2x^3+x^2+x-3=0 | | 7v+4=4(v+4) | | -x^4+2x^3+x^2+x-2=0 | | 9/q=9 | | 4a-8a=6a | | |-3x-1|=7 | | x+47+2x=x+69 | | -3(w-3)=7w+39 | | 2n(n+5)=-4(n+5) | | 11x+25y=180 | | -20y=25y | | 2y-4=-3(y+8) | | 7n^2-35n-98=0 | | 25y=50 | | 15/60=n/6 | | 25=50 | | (2x+40)*(x+6)=4x^2 | | 2x+1=9x-1 | | 0.25(5+x)+0.75(x+1)=2.5 | | 2(w+6)=-7+30 | | F(6)=8 | | 4n^2-16n=44 | | 15+6r=7(4r-1) |

Equations solver categories